Downregulated GABA and BDNF-TrkB Pathway in Chronic Cyclothiazide Seizure Model - Shuzhen Kong; Zhihua Cheng; Jianhui Liu; Yun Wang (Neural Plasticity)
Cyclothiazide (CTZ) has been reported to simultaneously enhance glutamate receptor excitation and inhibit GABAA receptor inhibition, and in turn it evokes epileptiform activities in hippocampal neurons. It has also been shown to acutely induce epileptic seizure behavior in freely moving rats. However, whether CTZ induced seizure rats could develop to have recurrent seizure still remains unknown. In the current study, we demonstrated that 46% of the CTZ induced seizure rats developed to have recurrent seizure behavior as well as epileptic EEG with a starting latency between 2 weeks and several months. In those chronic seizure rats 6 months after the seizure induction by the CTZ, our immunohistochemistry results showed that both GAD and GAT-1 were significantly decreased across CA1, CA3, and dentate gyrus area of the hippocampus studied. In addition, both BDNF and its receptor TrkB were also decreased in hippocampus of the chronic CTZ seizure rats. Our results indicate that CTZ induced seizure is capable of developing to have recurrent seizure, and the decreased GABA synthesis and transport as well as the impaired BDNF-TrkB signaling pathway may contribute to the development of the recurrent seizure. Thus, CTZ seizure rats may provide a novel animal model for epilepsy study and anticonvulsant drug testing in the future.